ChemInform Abstract: Heterogeneous Cobalt Catalysts for the Acceptorless Dehydrogenation of Alcohols. Issue 19 (18th April 2013) - Shimizu, Ken‐ichi; Kon, Kenichi; Seto, Mayumi; Shimura, Katsuya; Yamazaki, Hiroshi; Kondo, Junko N.
Abstract A Co/TiO2 catalyst shows high activity in the dehydrogenation of various secondary alcohols (I) and (III) to afford the corresponding ketones.